Cultural Plunder by the Einsatzstab Reichsleiter Rosenberg : Database of Art Objects at the Jeu de Paume - Bundesarchiv (2010)
[Dt.:] Die Datenbank führt zum ersten Mal die verbliebenen Registrierungskarten und Fotografien der ERR zusammen, des Einsatzstabes Reichsleiter Rosenberg, welcher unter Alfred Rosenberg kulturelle Wertgegenstände von den Juden während des Zweiten Weltkrieges geplündertet haben, z.B. aus Deutschland, Frankreich und Belgien. Die Datenbank umfasst merh als 20.000 Kunstgegenstände, die entweder nach Einzelobjekten oder nach ehemaligen Besitzern geordnet sind. Die Webseite beinhaltet ebenfalls historische Informationen über räumliche Verbreitung der gestohlenen Objekte. - [Engl.:] This database brings together for the first time in searchable illustrated form the remaining registration cards and photographs produced by the ERR - the Special Task Force leading by Alfred Rosenberg who plundered cultural valuables from the Jewish in Nazi-occupied countries during the Second World War, such as Germany, France and Belgium. The database covers more than 20,000 art objects searchable by individual objects and by the owners from whom these objects were taken. The webpage also contains historical information about the spatial distribution of the looted objects.